The Frequency of Detection and Characteristics of Trombocytopathy at Different Stages of Pregnancy - Zaynutdinova D.L; Keldibekov Sh.O; G’ulomova Sh.X; Ibrohimova D.I; Avazova Sh.A. (Zien Journals, 2022)
The research has focused on the frequency, causes and consequences of thrombocytopathies acquired at all stages of pregnancy. The purpose of which was identification of the frequency and characteristics of thrombocytopathies at different stages of pregnancy. Clinical material for the study was obtained from 30 pregnant women aged 18-35 years who were treated from January 2021 to March 2022 in the department of pathology of pregnant women of the Tashkent Medical Clinic of the Ministry of Health of the Republic of Uzbekistan.
Keywords: pregnancy; thrombocytopathy; adhesion and aggregation; bleeding